2016
DOI: 10.18632/oncotarget.9377
|View full text |Cite
|
Sign up to set email alerts
|

Methylation-mediated repression of microRNA-129-2 suppresses cell aggressiveness by inhibiting high mobility group box 1 in human hepatocellular carcinoma

Abstract: Aberrant expression of microRNAs (miRNAs) and its dysfunction have been revealed as crucial modulators of cancer initiation and progression. MiR-129-2 has been reported to play a tumor suppressive role in different human malignancies. Here, we demonstrated that miR-129-2 was significantly decreased in hepatocellular carcinoma (HCC) tissues and cell lines. Furthermore, miR-129-2 was expressed at significant lower levels in aggressive and recurrent tumor tissues. Clinical analysis indicated that miR-129-2 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 43 publications
2
49
0
Order By: Relevance
“…Further investigation revealed that overexpression of HMGB1 impaired the suppressive effects of miR-34a on the CSCC cell proliferation, migration and invasion, which confirms this speculation. In addition, certain other miRs have also been demonstrated to directly target HMGB1, including miR-142 (23), miR-126 (24), miR-181 (25), miR-218 (26), miR-129 (27), miR-24 (28) and miR-141 (29). Therefore, the findings of the present study further expand the understanding of the regulatory mechanism of miRs/HMGB1 signaling in human cancer.…”
Section: Discussionsupporting
confidence: 55%
“…Further investigation revealed that overexpression of HMGB1 impaired the suppressive effects of miR-34a on the CSCC cell proliferation, migration and invasion, which confirms this speculation. In addition, certain other miRs have also been demonstrated to directly target HMGB1, including miR-142 (23), miR-126 (24), miR-181 (25), miR-218 (26), miR-129 (27), miR-24 (28) and miR-141 (29). Therefore, the findings of the present study further expand the understanding of the regulatory mechanism of miRs/HMGB1 signaling in human cancer.…”
Section: Discussionsupporting
confidence: 55%
“…Numerous studies have demonstrated that aberrant miRNAs are involved in cancer initiation, development and progression (22,23), including cervical cancer (CC). miRNAs have been identified as novel prognostic biomarkers and effective therapeutic targets of CC.…”
Section: Discussionmentioning
confidence: 99%
“…QRT-PCR was conducted as reported previously [35, 36]. All RNA was extracted based on the protocol of TRIzol reagent (Invitrogen, Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Then applying the biotinylated secondary antibodies (Goldenbridge, Zhongshan,China) according to SP-IHC assays.. Specific experiment was conducted similar to previously reported [35, 36]. …”
Section: Methodsmentioning
confidence: 99%